PERILAKU KEHIDUPAN ANAK DI PERKOTAAN DENGAN SEKOLAH SAMBIL BEKERJA - Rusli, aditya (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2024)
This article emphasizes on the theoretical aspect regarding the problem of school age children that go to work. Explanations referred to definitions proposed by scholars, and authorized legal institutions that are responsible for the management and the building of children’s education. Economic reasons and poverty certainly were the background and the most dominant cause that made these children went to work. In addition, psychological factors such as motivation, interest, etc were other internal factors involved.